Kegagalan Keberlanjutan Paradiplomasi dan Network Governance: Studi Kasus Sister City Kabupaten Sidoarjo – Kota Jinan Tiongkok - Sukma Ayu Putri Ariningtyas (Journal of Governance Innovation, 2024)
The sister city collaboration between Sidoarjo and Jinan has started since signing Letter of Intent (LoI) in 2010. This collaboration based on resemblance as industrial city that both have specialism on processing leather-based handicraft. Resemblance of characteristics, geography, and political ideology between two regions stimulate sister city collaboration. In the age of globalisation, relationship among actors on sister city are fundamentally for local governments partnership and sharing resources to realize public needs and regional development. This study uses qualitative research based on literature review from previous research about sister city initiatives and paradiplomacy. This study analyses the sister city between Sidoarjo and Jinan was ended even potentially on multisector improvement and strategic programs. Reinforcing factors are analyzed through the perspective of paradiplomacy and network governance, which findings that sustainable connectivity underlying sister city are determined by involvement of non-state actors, communication and lobbying, regent initiatives, and supportive policies.